Tradução como ponte plástica : hibridismo e identidade em verbetes da Wikipédia - Ribeiro, Patrick de Rezende (2013)
This paper presents the concepts of translation broadly, breaking with the conception that focuses on the transformation of a message in a certain language code into another, in which a merely literal equivalence is searched. This work has its theoretical basis around the postcolonial and deconstructionist theories focusing on Bhabha (2010), Hall (2006), Derrida (2006), Ottoni (2005), Orlandi (2008) and Niranjana (2011), which leads us to the possibility of rethinking the role of translation, understanding it as plastic bridges, a tool to deconstruct dominant paradigms and, consequently, retell stories and histories. Thus, it is aimed to think of translation in its plasticity, promoting bridges that express intersections among languages, showing the position of the human beings as the result of the crossing of several subjects. As the empirical object of analysis, three entries from the Wikipedia website were chosen. All of them present traces of Brazilian identity and it is aimed to investigate the nuances in the translation processes that can contribute to the way that Brazil is represented both by local and foreign communities, leading to the formation of stereotypes. This part of the work is also based on the stereoscopic reading and the Theory of Relevance proposed by Sperber & Wilson (2001). This research becomes relevant once study a corpus unexplored academically but socially in vogue, since the website Wikipedia is among the ten most accessed worldwide, with over 300 million unique access, besides the importance of being a source of collective construction of knowledge, reinventing the concept of encyclopedia. The research also becomes relevant from the perspective of translation studies once it discusses about the importance of the translator as tool for identity formation in different levels. It is also part of this study propose the hybrid concept of translation-review as a trend of the contemporary multilingual world.